Exploring the Molecular Mechanism of Niuxi-Mugua Formula in Treating Coronavirus Disease 2019 via Network Pharmacology, Computational Biology, and Surface Plasmon Resonance Verification - Wang, Wei; Cao, Xu; Cao, Yi-nan; Liu, Lian-lian; Zhang, Shu-ling; Qi, Wen-ying; Zhang, Jia-xin; Yang, Xian-zhao; Li, Xiao-ke; Zao, Xiao-bin; Ye, Yong-an (Current Computer - Aided Drug Design, 2024)
BackgroundIn China, Niuxi-Mugua formula (NMF) has been widely used to prevent and treat coronavirus disease 2019 (COVID-19). However, the mechanism of NMF for treating COVID-19 is not yet fully understood.ObjectivesThis study aimed to explore the potential mechanism of NMF for treating COVID-19 by network pharmacology, computational biology, and surface plasmon resonance (SPR) verification.Materials and MethodsThe NMF-compound-target network was constructed to screen the key compounds, and the Molecular Complex Detection (MCODE) tool was used to screen the preliminary key genes. The overlapped genes (OGEs) and the preliminary key genes were further analyzed by enrichment analysis. Then, the correlation analysis of immune signatures and the preliminary key genes was performed. Molecular docking and molecular dynamic (MD) simulation assays were applied to clarify the interactions between key compounds and key genes. Moreover, the SPR interaction experiment was used for further affinity kinetic verification.ResultsLipid and atherosclerosis, TNF, IL-17, and NF-kappa B signaling pathways were the main pathways of NMF in the treatment of COVID-19. There was a positive correlation between almost the majority of immune signatures and all preliminary key genes. The key compounds and the key genes were screened out, and they were involved in the main pathways of NMF for treating COVID-19. Moreover, the binding affinities of most key compounds binding to key genes were good, and IL1B-Quercetin had the best binding stability. SPR analysis further demonstrated that IL1B-Quercetin showed good binding affinity.ConclusionOur findings provided theoretical grounds for NMF in the treatment of COVID-19.
Keywords: Niuxi-Mugua formula